Impact of Indian Drama’s on Pakistani Culture: A Study on Women's Perspectives (Journal of Asian Development Studies, 2023)
This study investigates the impact of Indian dramas on Pakistani culture, explicitly emphasizing the perspectives of women aged 16 to 26. The research employed a survey questionnaire comprising one open-ended and 17 closed-ended questions, distributed to a sample of women from diverse educational institutions in Karak, Pakistan. With a response rate of 100%, the study findings highlight the topic's significance. The results reveal that a significant proportion of Pakistani women watch Indian dramas on television, indicating a strong influence on cultural preferences. However, the study also identifies negative impacts on social and cultural values. Respondents expressed concerns regarding language, dress, food, and cultural identity. These findings underscore the importance of promoting and preserving local culture through various avenues, including television programming, community activities, educational materials, and government initiatives. Recommendations include empowering women in cultural preservation efforts and strengthening regulatory measures to safeguard Pakistani culture. By implementing these recommendations, Pakistan can preserve its unique cultural heritage while fostering appreciation and understanding among its citizens. These insights contribute to the broader understanding of the influence of media on cultural dynamics, particularly from the perspective of Pakistani women.